Preparing Net Gen pre-service teachers for digital native classrooms - Ekiaka Nzai, Valentin; Feng, Yu-Lin; Reyna, Concepción (Colombian Applied Linguistics Journal, 2014)
This paper explores Net Gen pre-service teachers’ perspectives of future digital native classrooms based on the National Education Technology Plan (U.S. Department of Education, 2010). Participants were seven Net Gen pre-service teachers enrolled in a semester-long laboratory of practice project for Literacy Development for English Language Learners. Data were collected using a narrative strategy (Ginsburg, cited in Riessman, 1993) which consisted of analyzing information from participants’ life stories produced during two audiotaped focus group conversations. Findings showed that pre-service teachers had positive perceptions and beliefs toward the laboratory of practices based on the experimental cyberlearning workstation framework designed by the authors. The hands-on experiences helped them enhance their digital native-like citizenship in order to meet future students’ individual abilities and learning styles, and to encourage teaching with digital technologies. Some recommendations and limitations are also addressed.